Pengaruh Latihan Footwork Shuttle Run Terhadap Teknik PukulanForehand PermainanBulutangkis Pada Siswa Ekstrakurikuler SMA Negeri 3 Palopo - Maulana Saputra; Nur, Suaib; Hidayat, Rachmat; Jalil, Rasyidah (Universitas Hamzanwadi, 2025)
This study aims to determine the effect of shuttle run footwork training on improving forehand stroke technique in badminton. The research method used is an experimental method with a one-group pretest-posttest design. The population in this study consisted of 20 students, with 15 students selected as samples through purposive sampling. The instrument used was a forehand stroke technique skill test. Data analysis was carried out using descriptive statistics. The normality test results showed that the pretest data had a significance value of 0.572 (> 0.05), and the posttest data had a significance value of 0.680 (> 0.05), indicating that the data were normally distributed. The homogeneity test yielded a significance value of 0.613 (> 0.05), indicating that the data were homogeneous. The hypothesis test using a paired sample t-test showed a significance value (2-tailed) of 0.000 (< 0.05), with a t count of 41.402, which was greater than the t table value of 27.751. Therefore, it can be concluded that shuttle run footwork training has a significant effect on improving forehand stroke technique among badminton extracurricular students at SMA Negeri 3 Palopo.